HAK PREROGATIF PRESIDEN MENURUT UUD 1945 - Johansyah, Johansyah (Solusi, 2018)
In practice the power of the President of the Republic of Indonesia as head of state is often referred to as the "President's prerogative" and is defined as the absolute power of the President that cannot be disturbed by other parties. Theoretically, prerogative is translated as a privilege owned by certain institutions that are independent and absolute in the sense that they cannot be sued by other state institutions. In the modern state government system, this right is owned by the head of state, either the king or the president and head of government in certain fields stated in the constitution. This right is also matched with the full authority granted by the constitution to the executive body within the scope of the power of its government. The system of government of modern states seeks to place all models of power within the framework of public accountability. Thus, power that cannot be controlled, is sued and accounted for, in practice it is difficult to get a place. Thus, in the practice of state administration of modern countries, this prerogative is no longer absolute and independent, except in terms of policy making in the context of governance